Gambaran Kasus Spina Bifida di RSUD Arifin Achmad Provinsi Riau Periode 2015-2017 - Syntha Novianti Rahmad; Andrea Valentino; Huriatul Masdar (Jurnal Ilmu Kedokteran, 2020)
Spina bifida is a fault in the development of spine and the bones around until it leaves gap or defect in the spine. About 36 cases of spina bifida were involved in this research. The characteristis of spina bifida patients, mostly occurs at the patients at the age of > 28 days (83,3%). Most of them were male (52,8%). The most frequent spina bifida patients were the second child (44,4%) and location where spina bifida occurs were at the lumbosakral (72,2%). Classified into spina bifida aperta type (86,1%). The highest age of patients’ mother suffering from spina bifida was at the age of  20-40 (80,6%). In general, rupture didn’t occur on spina bifida patients (94.4%). The weight of spina bifida patients were between 2.500-4.000 gr (94,4%) and they didn’t have other congenital abnormalities (47,2%). The most gestational age of spina bifida patients’ mothers when giving birth were, is at 28-40 weeks (94.4%).